2019
DOI: 10.1002/bsd2.57
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' corporate social responsibility and corporate ability associations as predictors of reputation: Developing countries under analysis

Abstract: This study investigates the effect of corporate social responsibility (CSR) and corporate ability (CA) associations on perceived corporate reputation (PCR) and the relationship between the two associations in different cultural environments. By focusing on electricity providers, we carried out a questionnaire survey within BRICS capital cities—that is, Brazil, Russia, India, China, and South Africa—and tested a conceptual model via structural equation modelling. Results showed that, grouping BRICS together, CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 93 publications
(175 reference statements)
0
5
0
Order By: Relevance
“…The literature stream has found that customers take into consideration a firm's CSR actions when making consumption decisions (Rajaobelina et al, 2018;Shah and Khan, 2019). CSR practices of the firms improve corporate reputation (Contini et al, 2019) financial and organizational performance (Ali et al, 2019;Farooq and Salam, 2020), marketing and behavioral outcomes (Moliner et al, 2019;Ahmed et al, 2020), customer co-creation behavior (Luu, 2019) and other in-role and extra-role behaviors (Silva et al, 2020). However, customer perceptions of CSR activities and its effect on customer behavior are the latest field and more evidence is needed to fill the gap in the literature about CSR and customer behavior outcomes (Uhlig et al, 2019;Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The literature stream has found that customers take into consideration a firm's CSR actions when making consumption decisions (Rajaobelina et al, 2018;Shah and Khan, 2019). CSR practices of the firms improve corporate reputation (Contini et al, 2019) financial and organizational performance (Ali et al, 2019;Farooq and Salam, 2020), marketing and behavioral outcomes (Moliner et al, 2019;Ahmed et al, 2020), customer co-creation behavior (Luu, 2019) and other in-role and extra-role behaviors (Silva et al, 2020). However, customer perceptions of CSR activities and its effect on customer behavior are the latest field and more evidence is needed to fill the gap in the literature about CSR and customer behavior outcomes (Uhlig et al, 2019;Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…3) A constant commitment of business to ethical manners and contribution to economic development, while improving the quality of life of its employees and their families, as well as of society at large (Baltacheyeva & Torba, 2017;Bataeva et al, 2018;Contini et al, 2019).…”
Section: The Essence Of Social Responsibility Of Businessmentioning
confidence: 99%
“…Several internationally held surveys have expressed that customers' responses are positive/optimistic toward products manufactured by socially responsible organizations (Bhattacharya & Sen 2004). Further studies argued that companies involved in CSR practices fetch several benefits; for instance, in their study, Contini et al, 2019 found that companies practicing CSR have an excellent reputation in the market. The performance of the company enhances (Farooq & Salam, 2020; Ali et al, 2019), gain in market share and customer base (Ahmed et al, 2020; Moliner et al, 2019), and PI and recommendation to others (Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several internationally held surveys have expressed that customers' responses are positive/optimistic toward products manufactured by socially responsible organizations (Bhattacharya & Sen 2004). Further studies argued that companies involved in CSR practices fetch several benefits; for instance, in their study, Contini et al, 2019 found that companies practicing CSR have an excellent reputation in the market.…”
Section: Introductionmentioning
confidence: 99%